EMTs and GPs: what do we think of each other?. Issue 7 (22nd June 2006) - Bury, G; Egan, M; Reddy, L
Abstract : Background: Ireland's health services are undergoing dramatic reorganisation. The establishment of general practitioner (GP) out of hours cooperatives and the integration of current ambulance services into a national ambulance service are among the issues that will impact on prehospital care of emergencies. The study aimed to explore the perceptions of GPs and emergency medical technicians (EMTs) of their own and each other's roles in the context of such reforms. Methods: A census of all GPs (511) and EMTs (301) in three of Ireland's eight health board regions was undertaken. A questionnaire containing 31 statements asked respondents to indicate their agreement (or lack of it) in areas such as general relationships, care, and training, roles in emergencies and future developments. Results: Of the personnel contacted, 72% of GPs and 75% of EMTs responded. They report excellent working relationships, agree that the ambulance service is of high quality, and that GPs are willing to provide care in emergencies. However, working links are less satisfactory for EMTs, who report a far higher perception of GP use of emergency ambulances than reported by GPs. Both groups are interested in innovative future links. Discussion: Convergence between the professional groups in different geographic areas and between the disciplines across the areas is striking. They include areas of satisfaction and dissatisfaction. The need for improved liaison between the disciplines is clear.